Analysis of Physics Learning Outcomes in Terms of Student Learning Habits - Fitri April Yanti; Anatri Desstya; Ryzal Perdana (Universitas Pendidikan Mandalika, 2021)
This study aims to determine: (1) the level of suitability of students' physics learning habits, (2) the level of suitability of students' physics learning outcomes in terms of students' learning habits. Descriptive research method is used in this research. The research sample consisted of 30 grade VII students of SMP PGRI 3 Sekampung which were obtained through proportional random sampling technique. The test method is used to obtain data on learning outcomes. Questionnaire and interview methods were used to obtain data on the results of learning habits. Data were analyzed using scoring with good, moderate, and poor criteria. The results showed that: (1) grade VII students of SMP PGRI 3 Sekampung had